Position-Specific Body Composition Trend in Football: A Comparative Study - Inderjit Singh & Dr. Manohar Lal (Cuestiones de Fisioterapia, 2025)
This study explores body composition trends in players categorized into the respective positions: forwards, midfielders, defenders/goalkeepers. Body composition—fat mass, lean mass, and skeletal muscle—affects athletic performance, and considering its position-specific variations can allow for optimized training and reduce injury. Purposive sampling was used to select 200 players (18-28 years of age) from the Punjab Football Association.